PENGARUH KUALITAS LAYANAN CITRA INSTITUSI TERHADAP KEPUASAN YANG DIMEDIASI LOYALITAS MAHASISWA: (Studi pada Magister Administrasi Publik Universitas Brawijaya) - Juviano Noe Ribeiro (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
This study aims to determine the effect of service quality and institutional image on student loyalty through student satisfaction (Study on Master of Public Administration, University of Brawijaya). This research is a quantitative research with survey techniques. The sample in this study was students of the 2018-2020 public administration master’s program. The sample collection technique used was purposive sampling with a total sample of 136 samples. The data analysis technique used is Structural Equation Modeling and Partial Least Square (SEM-PLS) with an analysis tool using Smart-PLS 3.0. The results of this study indicate that service quality has no effect on student satisfaction, constitutional image has a positive and significant effect on student satisfaction, service quality has a positive and significant effect on student satisfaction, institutional image has a positive and significant effect on student loyalty, satisfaction has a positive and significant effect on loyalty student, service quality has no effect on student loyalty and institutional image has a positive and significant effect on student loyalty.